Parenting and its educational and psychological effects on children in the Emirati society - Al Tamimi, Mashael (Al-Adab Journal, 2025)
This research aims to study the effects of parental separation on children in the UAE community from its educational and psychological aspects, highlighting the challenges that children face as a result of this separation. The research addresses the impact of separation on children's psychological stability, including problems of anxiety, depression and behavioral disorders, in addition to its impact on their academic performance and academic achievement. The research also explores the role of the UAE community, including educational and social institutions, in supporting children affected by their parents' separation, and provides recommendations for developing effective strategies to mitigate the negative effects of this phenomenon. Data and information derived from previous studies and field research are analyzed to provide a comprehensive picture of the size and impact of the problem in the cultural and social context of the UAE. The research results showed that parental separation leads to psychological and behavioral problems among children in the UAE community, which negatively affects their academic achievement and social relationships. The main recommendations include enhancing psychological support for children and educating parents on how to deal with the effects of separation. It is also recommended to activate the role of schools in monitoring children's behavior and providing the necessary support, in addition to updating legislation to ensure a stable and safe environment for them. Encouraging continuous research in this area is important for developing effective strategies to deal with this phenomenon.